A Recombinase Polymerase Amplification-Coupled Cas12a Mutant-Based Module for Efficient Detection of Streptomycin-Resistant Mutations in Mycobacterium tuberculosis - Liu, Peng; Wang, Xinjie; Liang, Juan; Dong, Qian; Zhang, Jinping; Liu, Dongxin; Wang, Shuai; Bi, Jing; Liu, Wenqi; Wang, Zhaoqin; Chen, Liang; Liu, Lei; et al. (Frontiers in Microbiology, 2022)
Drug-resistant tuberculosis (TB) is a serious public health problem and threat to global TB prevention and control. Streptomycin (STR) is the earliest and classical anti-TB drug and the earliest drug that generated resistance to anti-TB treatment, which limits its use in treating TB and impedes TB control efforts. The rapid, economical, and highly sensitive detection of STR-resistant TB may help reduce disease transmission and morbimortality. CRISPR/CRISPR-associated protein (Cas) is a new-generation pathogen detection method that can detect single-nucleotide polymorphisms with high sensitivity and good specificity. In this study, a Cas12a RR detection system that can recognize more non-traditional protospacer-adjacent motif targeting sequences was developed based on Cas12a combined with recombinase polymerase amplification technology. This system detects 0.1% of the target substance, and the entire detection process can be completed within 60 min. Its sensitivity and specificity for detecting clinical STR-resistant M.tb were both 100%. Overall, the Cas12 RR detection system provides a novel alternative for the rapid, simple, sensitive, and speciﬁc detection of STR-resistant TB, which may contribute to the prompt treatment and prevention of disease transmission in STR-resistant TB.